Barbarossa − Bar(bar)ossa − Barbossa: The permanence of the Black Legend as a discourse of otherness - Leetoy, Salvador (2018)
This article explores contemporary cultural appropriations of the Black Legend, a 16th and 17th century narrative used as a propagandistic strategy addressed to criticize Spain’s imperial mission in America. First, this article reviews geopolitical reasons that prompted politics of representation against Spain. It is argued that these forms of representation were aimed to identify Spain as an internal Other opposite to any European civilizing project. In the second part of this article, contemporary appropriations of the Black Legend are analyzed to show how this discourse is still present in stereotypes and clichés of a variety of cultural products. Accordingly, politics of representation of the film series of The Pirates of the Caribbean is reviewed.